Domestication of marine rotifer brachionus plicatilis in extensive culture system at low saltnities / Nuranith Athirah Ahmad Razak - Ahmad Razak, Nuranith Athirah (2020)
Rotifers are among the smallest metazoa in the world that have their own uniqueness. This research was conducted in order to find out if Brachionus plicatilis really can keep the best endurance towards the changes of salinity and does the changes of salinity will give effect towards growth rate of the rotifer species. The main aims for this study was to identify either the changes of the salinity give effects towards the growth rate of the Brachionus plicatilis. The second aim was to identify the best salinity for the growth rate of the Brachionus plicatilis and last but not least to produce mass production of Brachionus plicatilis. Generally, a batch culture method was used for the culturing of the rotifers. There were two batch culture where the first batch rotifer was cultured in20 ml of sea water while the second batch rotifer was cultured in 10 ml of sea water. A salinities of 12, 9, 5 and 0 ppt were applied to the second batch culture. The result obtained proved that the salinity does give effect towards the growth rate of the rotifer. Based from the result, it also showed that the salinity of 12 ppt was the best and optimum salinity for culture of rotifer for the aquaculture industry. The mass production of the rotifer was also a success. As a conclusion, the changes in salinity does give effect to the rotifer as it affect their growth rate.